How Early Nutrition and Foundational Cognitive Skills Interconnect? Evidence from Two Developing Countries - Alan Sanchez; Marta Favara; Margaret Sheridan; Jere R. Behrman (Institute of Labor Economics (IZA), 2022)
While the long-term consequences of early stunting on educational attainment and on school achievement tests are well-known, there is scarce evidence about the specific mechanisms through which early stunting leads to poorer educational outcomes, especially in LMIC contexts. We use unique data collected in Ethiopia and Peru as part of the Young Lives to investigate the relationship between early undernutrition and four foundational cognitive skills, the first two of which measure executive functioning: working memory, inhibitory control, long-term memory, and implicit learning. We exploit the rich longitudinal data available to control for potential confounders at the household level and for time-invariant community characteristics and we use data for paired-siblings to obtain household fixed-effects estimates. We find that stunting is negatively related with the development of executive functions, predicting reductions in working memory and inhibitory control by 12.6% and 5.8% of a standard deviation.
Keywords: I15; I25; J24; 330; foundational cognitive skills; early nutrition; executive functions; Ethiopia; Peru